The effects of newcomer proactive behaviours on socialization outcomes: A meta‐analysis. Issue 1 (22nd October 2022) - Zhao, Teng; Liu, Jiayi; Zawacki, Alissa M.; Michel, Jesse S.; Li, Hairong
Abstract: Organizational researchers and practitioners have shown increasing interest in how newcomer proactivity contributes to socialization. This meta‐analysis synthesizes the existing empirical research that examines the relationships between frequently performed newcomer proactive behaviours (sensemaking, relationship building, positive framing and job change negotiation) and proximal and distal socialization outcomes. Proximal outcomes include role clarity, task mastery and social integration; distal outcomes include job performance, job satisfaction, organizational commitment and turnover intention. Based on 45 independent samples ( N  = 11, 508), proactive behaviours were found to be generally beneficial for newcomer socialization. Relative weight analyses identified positive framing as the strongest predictor of five of the seven reviewed outcomes while relationship building accounted for the greatest part of the variance in social integration. Job change negotiation was the weakest predictor of socialization outcomes. The study also explored the impact of boundary conditions, including culture, study design and sample type, on the magnitude of these effects. The paper concludes by discussing the theoretical and practical implications of these findings, along with the study's limitations and suggestions for future research.